The Assessment of the Relationship Between Genetic Determinants of Migraine and Thyroid Dysfunction - Review - Kwiecień, Justyna; Getka, Beata; Łata, Michał; Przyborowska, Kinga; Wiejak, Katarzyna; Rukat, Mateusz (Journal of Education, Health and Sport, 2024)
Introduction and objective: The purpose of this paper is a systematic review of articles and research in the context of the relationship between genetic determinants of migraine and thyroid dysfunction. Materials and methods: A non-systematic review of the scientific literature was carried out according to the following keywords: PubMed was searched and 76 articles published up to 2023 were analyzed. Description of the state of knowledge: Epidemiological studies confirm the co-occurrence of migraine and thyroid dysfunction, especially hypothyroidism, which are considered to be diseases with a strong genetic background. Thyroid function parameters such as TSH and fT4 are susceptible to genetic influences. However, there is a lack of consistent interpretation of the observational results, which highlights the need for further research. Analysis of gene overlaps and links between headache and thyroid function, based on GWAS data, could shed light on the complex genetic interactions underlying this association. Summary: The genetic associations revealed in the study enhance our comprehension of the intricate relationship between migraine and thyroid dysfunction. These findings not only offer the prospect of developing biomarkers for identifying migraine patients who might benefit from thyroid hormone therapy but also underscore the promising potential of future genetic studies in providing biological insights to advance clinical decision-making in understanding and addressing these interconnected phenomena.